PERCEPTIONS AND EXPERIENCES OF ELDERLY RESIDENTS IN A NURSING HOME - Renata Alessandra Evangelista; Alexandre de Assis Bueno; Paulo Alexandre de Castro; Jessica Neto Nascimento; Neilene Teixeira de Araújo; Graciele Pereira Aires (SciELO, 2014)
The objective of this study was to evaluate the perception of the elderly residents of a long-stay nursing home on the process of institutionalization. We interviewed 14 subjects, five women and nine men, aged between 60 and 92 years. Data collection was conducted with a semi-structured sociodemographic interview, which presented the guiding question: "Tell me about how is your life, what do you do and how did you come to live here". From the analysis, we found topics related to feelings of abandonment, loneliness, anger, ingratitude, living with chronic pain, satisfaction of property in the nursing home, productivity and social relationship. Given the thematic analysis, it was possible to group them into three categories such as: what the elderly feel, what the elderly perceive and what the elderly desire. As a result, we need public policies that addresses to the service provided by institutions regarding elderly expectations.